Questioning the moral understanding of law - Marijan Pavčnik (DANUBE: Law, Economics and Social Issues Review, 2017)
The primary content-related framework we are bound to are the basic human rights as established in the constitution. These basic rights may change and develop, yet as the heritage of our political and legal culture, they possess such a solid core meaning that only a "dogmatic sceptic" (G. Radbruch) can doubt it. In societies with plural values, the moral values expressed by the basic human rights are the most solid moral basis of law. The moral understanding of law is necessarily accompanied by a moral criticism of law. Such criticism is often not pleasing to the authorities, but it cannot be avoided if one wants to live up to our responsibility towards nature, society and future generations. A lawyer who is not interested in these issues and only sticks to the letter of the law acts in a fossilized manner and does not enrich the life that the law is intended for. Legal thought should always have its meaning, as Smole's Antigone would say.
Keywords: 330; Moral Understanding of Law; Legal Positivism; Basic Human Rights; Moral Charge of Law; Acting lege artis; Moral Criticism of Law